2023
DOI: 10.3390/cancers15082315
|View full text |Cite
|
Sign up to set email alerts
|

E. coli Phagelysate: A Primer to Enhance Nanoparticles and Drug Deliveries in Tumor

Abstract: The tumor microenvironment (TME), where cancer cells reside, plays a crucial role in cancer progression and metastasis. It maintains an immunosuppressive state in many tumors and regulates the differentiation of precursor monocytes into M1 (anti-tumor)- and M2 (pro-tumor)-polarized macrophages, and greatly reduces anticancer drug and nanoparticle delivery. As a result, the effectiveness of recently developed chemo- and/or nanotechnology-mediated immune and magnetic nanoparticle hyperthermia (mNPH) therapies is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Numerous studies in bacterial-mediated tumor therapy effectively reverse tumor immunosuppression and significantly enhances the effect of tumor immunotherapy by polarizing TAMs to the M1 type. 17 , 28 , 29 Therefore, we examined the polarization phenotype of RAW264.7 cells after VNP-IFNβ stimulation via flow cytometry in vitro , and the results showed that the expression level of CD86 in RAW264.7 cells was much higher than that in the PBS group (11.8% vs. 2.9%) and the VNP group (11.8% vs. 8.9%) ( Figures 2 C and 2D), which suggests that VNP-IFNβ can promote the macrophage polarization to M1 antitumor phenotype. Next, we examined the expression levels of different polarization markers of RAW264.7 cells after VNP-IFNβ stimulation via RT-PCR in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies in bacterial-mediated tumor therapy effectively reverse tumor immunosuppression and significantly enhances the effect of tumor immunotherapy by polarizing TAMs to the M1 type. 17 , 28 , 29 Therefore, we examined the polarization phenotype of RAW264.7 cells after VNP-IFNβ stimulation via flow cytometry in vitro , and the results showed that the expression level of CD86 in RAW264.7 cells was much higher than that in the PBS group (11.8% vs. 2.9%) and the VNP group (11.8% vs. 8.9%) ( Figures 2 C and 2D), which suggests that VNP-IFNβ can promote the macrophage polarization to M1 antitumor phenotype. Next, we examined the expression levels of different polarization markers of RAW264.7 cells after VNP-IFNβ stimulation via RT-PCR in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…E. coli phage lysate can modify the TME, transforming tumor-associated M2 macrophages into anti-tumor M1 macrophages. Bacterial phage lysates (BPLs) and phage/BPL-coated proteins can also modify the TME, eliciting robust anti-tumor responses and facilitating the conversion of M2-polarized TAMs to a more M1-polarized environment [156].…”
Section: Bacteriophages In Cancer Immunotherapymentioning
confidence: 99%